EMPLOYEE PERFORMANCE IMPROVEMENT STRATEGY THROUGH STRENGTHENING JOB CHARACTERISTICS, TRANSFORMATIONAL LEADERSHIP, AND WORK ATTITUDE AND WORK MOTIVATION - Ujo Sujoto; Anoesyirwan Moeins; Hamzah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to find strategies to improve the performance of First Expert Immigration Analysts at the Directorate General of Immigration at Soekarno-Hatta Airport through job characteristics, transformational leadership, and work attitudes, both directly and through the mediation of work motivation. The main focus is to identify the most effective way to develop employee motivation and performance through a multidimensional approach that includes individual factors, leadership, and the work environment. This study uses a mixed methods method, namely a combination of quantitative and qualitative approaches in data collection and analysis. The research location is at the Class I Immigration Office of Soekarno-Hatta Airport, which is administratively located in Banten Province. The focus of the research is on the role of Immigration Officers and First Expert Immigration Analysts. The study population was 406 people, with a sample of 202 people. This study concludes that job characteristics, transformational leadership, work attitudes, and work motivation have a direct and significant effect on employee performance. In addition, job characteristics, transformational leadership, and work attitudes also influence work motivation. Work motivation is proven to indirectly mediate the influence of these three variables on improving employee performance at the Directorate General of Immigration at Soekarno-Hatta Airport.